Cancer care commissioning, information and choice in England: a commentary (Italian Journal of Public Health, 2006)
The National Health Service in England has focused on improving cancer services over the last decade,following indications from the international EUROCARE study that cancer services, and survival, were behindother comparable countries. New managerial structures and processes have been created to encourageservice specialization by cancer type, develop coordination between hospitals and improve access times forpatients. However, within the NHS in England as a whole, the government has been encouraging marketideas that contrast with this centralist direction. To improve patient ‘choice’, an improved informationsystem, drawing on timely clinical and administrative data, is needed for cancer care commissioning.
Keywords: cancer; healthcare services; commissioning; information; choice